Tricks to do a quick successful bronchial artery embolization (BAE) in massive haemoptysis - Abdul Rahim, Ezamin; Muda, Ahmad Sobri; Jamil, Hariati (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Bronchial artery embolization (BAE) is the mainstay treatment for massive haemoptysis. Herein we briefly discuss the tips and tricks of super-selective embolization of bronchial artery using N-butyl-2 cyanoacrylate (NBCA). Based on our experience, this technique produces a better resolution and exhibit high non- recurrence rate in the treatment of massive haemoptysis.